Traumatic brain injury: A common neurosurgical entity - Ali, Mumtaz; Usman, Muhammad (Journal of Postgraduate Medical Institute, 2013)
Traumatic brain injury (TBI) is leading cause of death and disability worldwide. Every year about 1.5million affected people die and several millions receive emergency treatment. TBI with current best practice,results in only about one third of patients being able to live independently in the long term. Althoughpeople from all age groups may be affected; the TBI is more common in young age because of the exposureof this age to more chances of accidents on roads, work place and during leisure activities. Decompressivecraniectomy is a surgical operation to decrease intracranial pressure, has been used with increasingfrequency. Neurological surgeons however do not know whether the operation achieves its goalof improving patient outcomes. The question is considered of great importance internationally. In Pakistanand especially in the province of Khyber Pukhtunkhwa, firearm injuries are more common and childrenare more prone to fall. The incidence of TBI is on the rise in developing countries. Anything that canimprove the outcome from TBI has the potential of improving the lives of many head injured patients.